THE COST OF NOT BREASTFEEDING IN NORTH SUMATERA - Estro Dariatno Sihaloho (Universitas Negeri Medan, 2018)
Breastfeeding provide many good impacts on health and economics side. This study tries to estimate the economic impact of not breastfeeding due to diarrhea and PRD cases in North Sumatera. The economic impact elaborated by finds health system medical cost and the patient/non- medical cost. This paper calculates health system medical cost from public hospital, private hospital, and primary health center while the patient cost calculated from 135 patients in 3 kinds of health facilities. This paper combines primary data with Census Data 2010 and IDHS 2012 to get total cost of not breastfeeding in North Sumatera. The costing process shows there are economic loss about US1,290,582 with average cost about US 13.48 in North Sumatera. The total cost consist of health system perspective cost about US 799,050 and patient costs about 491,532. This show that most of the cost comes from the health system cost/medical cost about 61.91% and the 38.09% borne from the patient costs and non-medical cost